Herencia Cultural Italiana en la Pampa Gringa: el caso del escritor Gastón Gori (El Hilo de la Fabula, 2018)
The migratory phenomenon has led to Argentina over the course of almost two centuries —between the end of the nineteenth century and after the Second World War— 15 million of italians. Therefore, the Argentine identity is marked and constituted by immigration. This study is carried out with the aim of taking and maintaining an analytical look on the migratory literature of the Pampa Gringa area, looking for the traces of the migratory and Italian culture, that still color the mongrel and varied historical–literary panorama of Argentina. The author in which the present article is focused on is Gastón Gori, born in Esperanza in 1915, grandson of Friulian immigrants, known as the first writer of the phenomenon of immigration in the Pampa Gringa. The relationship between Italy and Argentina can also be translated into literary and academic links. Literature, as a privileged space for representation and history, is one of the channels through which we can become aware of the many different problems that are related to the migratory movement and of the  rigins and the identity’s searching of a community.
Keywords: Gastón Gori; Pampa Gringa; inmigration literature